Turner Syndrome, Uncommonly Diagnosed Cause of Short Stature: Case Report and Review of Literature - Basnet, S; Eleena, A; Sharma, AK (Journal of Nepal Paediatric Society, 2013)
Many children are frequently brought to the paediatric clinic for evaluation of short stature. Evaluation for these children does not go beyond x-ray for bone age estimation and growth hormone analysis. Most of them are considered having constitutional or genetic cause for their short stature. However, shuttle dysmorphic features could be missed in many of them. Hence, many children might be having chromosomal anomaly as an underlying cause. We report a case of 40 months who had been evaluated several times in the past for pneumonia, otitis media and short stature is finally diagnosed to have Turner syndrome. DOI: http://dx.doi.org/10.3126/jnps.v33i1.8174 J Nepal Paediatr Soc. 2013;33(1):74-76